Beyond Tradition: Digitizing Local Food Heritage for Ecosystem Efficiency in Thailand’s Eastern Economic Corridor - Ruangthip, Parinya; Rueboon, Wichien (Journal of Cultural Analysis and Social Change, 2025)
Food heritage plays a role in destination image, and it is also how tourism spending circulates within local communities, although small food producers and micro-entrepreneurs typically have no lasting digital presence and rather operate through shadowy intermediaries. This paper highlights a design-science study to create and evaluate a cross-platform, human-centered web application connecting local-based food producers and products in Thailand’s Eastern Economic Corridor. Based on a user-centered system development life cycle, the requirements were captured by stakeholder interviews, benchmarking existing platforms, and consulting with destination agencies and ICT partners, while they were organized according to the Business Model Canvas and personal-branding concepts. The browser-based artefact that’s been put together from this process gives vendors a way to showcase products, provenance stories, and branding assets; travelers to see what’s on offer in an area; locals to do the same; and administrators tools for curation and basic governance. Functional and structural testing was completed before pilot testing. An expert-vendor-resident-tourist mixed evaluation revealed high levels of perceived usefulness, information trust, power to use, and aesthetic quality (mean ratings of ≈3.8–3.9 on a five-point scale), with overall satisfaction falling in the “very good”/ “good” ranges and acceptable security perceptions. A searchable operator registry and early cross-vendor collaboration point to the formation of a business network for sharing knowledge and joint marketing. The study provides a reusable method to translate culinary heritage into a light regional platform for SME discoverability and reach, as well as an evaluative framework that connects perceived quality with destination agencies' ecosystem signals.